Persistent contamination, limited accumulation: In-situ isotope tracing reveals fast thallium turnover in natural waters - Chenghong Yu; Hongkai Wang; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Lihua Liu; Nengwang Chen; Minwei Xie (Aquatic Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Environmental impact and economic analysis of waste photovoltaic materials recycling: A multi-scenario analysis - Xuerou Sheng; Xueliang Yuan; Fanhua Rong; Leping Chen; Mengyue Liu; Jian Zuo; Qingsong Wang; Qiao Ma; Feifei Liu (Journal of Environmental Management, 2026)

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Simulating the multiple effects of a diatom bloom on metal bioaccumulation in clams - Weiyi He; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Marine Pollution Bulletin, 2025)

Refining marine metal biomonitoring through insights into allometry in green mussels - Yuqing Liao; Haiyan Xiong; Wenze Xiao; Jun Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Harnessing soybean okara for enhanced microbial production of indigoidine - Ziqiang Chen; Wenqing Liu; Shenyi Zhang; Yushen Song; Zixuan Zhang; Guanning Yao; Guang-Rong Zhao; Hongji Zhu; Di Zhang; Jianjun Qiao; Hui Zhao; Jiaheng Liu (Bioresource Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Inhibitory effects of different plant extracts on Histomonas meleagridis in vitro and in vivo in chickens - Qiao-Guang Chen; Shuang Wang; Jie Rong; Chen Chen; Zhao-Feng Hou; Dan-Dan Liu; Jian-Ping Tao; Jin-Jun Xu (Veterinary Parasitology, 2025)

Hidden threat in turbid waters: Quantifying and modeling the bioaccumulation and risks of particulate metals to clams - Jing Qian; Xue Cao; Haiyan Xiong; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Efficient preparation of cycloamylose from potato starch using recombinant 4-α-glucanotransferase - Yan Huang; Rong Zhu; Jiehu Liu; Xueyi Qiao; Bo Xu; Lei Wang; Lingqia Su (Systems Microbiology and Biomanufacturing, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Epiphytic mosses alter Pinus massoniana deadwood microbial and physicochemical properties thereby influencing the decomposition process - Bingyang Shi; Xiurong Wang; Shuoyuan Yang; Hongmei Chen; Yang Zhao; Qiao Liu; Rong Zou; Muyan Xie; Lixin Duan; Fang Liao (Plant and Soil, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Increasing spray volume and ozone spray of tetraconazole improve control against strawberry powdery mildew - Lili Jiang; Bingjie Liu; Shouan Zhang; Rong Zhang; Chong Wu; Kang Qiao (Crop Protection, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Graphene-based aerogels in water and air treatment: A review - Bin Gao; Xiangbo Feng; Yaofei Zhang; Zhuoxuan Zhou; Jiafeng Wei; Rong Qiao; Fukun Bi; Ning Liu; Xiaodong Zhang (Chemical Engineering Journal, 2024)

Boosting toluene deep oxidation by tuning metal-support interaction in MOF-derived Pd@ZrO2 catalysts: The role of interfacial interaction between Pd and ZrO2 - Fukun Bi; Shuting Ma; Bin Gao; Baolin Liu; Yuandong Huang; Rong Qiao; Xiaodong Zhang (Fuel, 2024)

NixSy/NF composites assembled by sulfidation of nickel foam (NF) for highly effective capture of iodine - Bo Qiao; Haiqing Yan; Chaonan Wang; Huiqin Yao; Zidan Cai; Keren Shi; Rong Liu; Shulan Ma (Chemical Engineering Journal, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Feeding-induced plant metabolite responses to a phoretic gall mite, its carrier psyllid and both, after detachment - Mengke Yang; Jianling Li; Haili Qiao; Kun Guo; Rong Xu; Hongshuang Wei; Jianhe Wei; Sai Liu; Changqing Xu (Experimental and Applied Acarology, 2023)

Potential candidate genes and pathways related to cytoplasmic male sterility in Dianthus spiculifolius as revealed by transcriptome analysis - Yingzhu Liu; Han Sun; Rong Ye; Jinxue Du; Haizhen Zhang; Aimin Zhou; Kun Qiao; Jingang Wang (Plant Cell Reports, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Extraction and characterization of waxy and normal barley β-glucans and their effects on waxy and normal barley starch pasting and degradation properties and mash filtration rate - Qiao Li; Juan Liu; Huisheng Zhai; Zhihui Zhang; Rong Xie; Futong Xiao; Xingquan Zeng; Yuhong Zhang; Zhongyi Li; Zhifen Pan (Carbohydrate Polymers, 2023)

Green supply chain management for a more sustainable manufacturing industry in China: a critical review - Xuerou Sheng; Leping Chen; Xueliang Yuan; Yuzhou Tang; Qian Yuan; Rong Chen; Qingsong Wang; Qiao Ma; Jian Zuo; Hongwei Liu (Environment, Development and Sustainability, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Benefit of Dietary Supplementation with Bacillus subtilis BYS2 on Growth Performance, Immune Response, and Disease Resistance of Broilers - Yunxiang Dong; Rong Li; Yu Liu; Lianying Ma; Jihua Zha; Xibo Qiao; Tongjie Chai; Bo Wu (Probiotics and Antimicrobial Proteins, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

To perceive a perfect Dora Maar in peripheral vision - Rong-Ding He; Tao Su; Yang Yang; Ying Liu; Yan Wei; Rong-Qiao He (Science China Life Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Distribution of olivine and pyroxene derived from Clementine data in Crater Copernicus - Fujiang Liu; Rong Yang; Ying Zhang; Le Qiao; Shun Wang; Yang Yang; Xiaopan Wang (Journal of Earth Science, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Design, Recombinant Expression, and Antibacterial Activity of the Cecropins–Melittin Hybrid Antimicrobial Peptides - Yu Cao; Rong Qing Yu; Yi Liu; Huo Xiang Zhou; Ling Ling Song; Yi Cao; Dai Rong Qiao (Current Microbiology, 2010)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

Cytogenetic Study of a Trigeneric (Triticale × Trileymus) Hybrid - Xing-Feng Li; Zhen-Qiao Song; Shu-Bing Liu; Ju-Rong Gao; Hong-Gang Wang (Euphytica, 2006)